Association between atypical endometriosis and ovarian malignancies in the real world - Kyeong A So; Sung Ran Hong; Nae Ri Kim; Eun Jung Yang; Seung-Hyuk Shim; Sun Joo Lee; Tae Jin Kim (BMC, 2021)
Abstract Background To evaluate the clinical outcome of atypical endometriosis and its association with ovarian malignancy. Methods This retrospective study included patients diagnosed with atypical endometriosis between January 2001 and December 2017. All patients had received surgical treatment for ovarian tumor. The clinical characteristics and histopathological results of all patients were reviewed. Results Atypical endometriosis was diagnosed in 101 patients. We analyzed 98 patients with a mean age of 34.8 years (range: 16-58 years). Ten patients (10.2%) had previously undergone endometriosis surgery more than once. In total, 12 (12.2%) patients had atypical endometriosis-associated ovarian malignancy-nine had carcinomas and three had borderline tumor. The tumors were pathologically classified as follows: five, clear cell carcinomas; two, endometrioid adenocarcinomas; one, mixed clear cell and endometrioid adenocarcinoma; one, seromucinous carcinoma; two, mucinous borderline tumors; and one, seromucinous borderline tumor. Conclusion Atypical endometriosis is most frequently associated with clear cell carcinoma and endometrioid adenocarcinoma. To identify the risk of ovarian malignancy and manage patients with endometriosis, diagnosing atypical endometriosis and recognizing its precancerous potential are important.